Recent advances in COPD disease management with fixed-dose long-acting combination therapies. (June 2014) - Bateman, Eric D; Mahler, Donald A; Vogelmeier, Claus F; Wedzicha, Jadwiga A; Patalano, Francesco; Banerji, Donald
<x xml:space="preserve">Abstract</x> Combinations of two long-acting bronchodilators and long-acting bronchodilators with inhaled corticosteroids (ICS) are recommended therapies in the management of chronic obstructive pulmonary disease (COPD). Three fixed-dose combination products have recently been approved for the treatment of COPD (the long-acting β2-agonist plus long-acting muscarinic antagonist [LABA/LAMA] combinations glycopyrronium/indacaterol [QVA149] and umeclidinium/vilanterol, and the LABA/ICS fluticasone furoate/vilanterol), with others currently in late-stage development. LABA/LAMA and LABA/ICS combination therapies demonstrate positive effects on both lung function and patient-reported outcomes, with significant improvements observed with LABA/LAMA combinations compared with placebo, each component alone and other comparators in current use. No new safety concerns have been observed with combinations of long-acting bronchodilators. Combinations of two long-acting bronchodilators represent a new and convenient treatment option in COPD. This review summarizes published efficacy and safety data from clinical trials of both LABA/LAMA and novel LABA/ICS combinations in patients with COPD.